Digital Design Method of Variable Ratio Tooth Profile of the Recirculating Ball Variable Ratio Steering - Hu Dawei; Niu Ziru; Tu Ming; Tan Jiangjiang; Yan Tianli; Qi Wang; Li Gangyan (Jixie chuandong)
In order to solve the design problem of variable ratio tooth profile of gear for the recirculating ball variable ratio steering,a digital design method is put forward,the Boolean reduction operation macro program is established based on variable ratio movement rule and the envelope surface generation machining processes of variable ratio tooth profile of gear is simulated in CATIA software,and the three dimensional model of variable ratio gear is generated. The tooth surface is repaired and the virtual assembly of variable ratio gear is completed,then the kinematics simulation analysis of variable- ratio rack and pinion meshing pair is carried out by using ADAMS software,the curve of simulation is analyzed and compared with the curve of designing,the effectiveness of the method is validated.